2018
DOI: 10.1002/jper.17-0665
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of progenitor cells from surgically created early healing alveolar defects in humans: A preliminary study

Abstract: Tissue removed from SC-EHAD is a possible source of progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…Studies have shown that the tissue present in healing sockets at the third to fourth week is rich in woven bone and immature osteoblasts [37,[42][43][44][45]. SC-EHAD cell characteristics suggest its osteoprogenitor nature [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the tissue present in healing sockets at the third to fourth week is rich in woven bone and immature osteoblasts [37,[42][43][44][45]. SC-EHAD cell characteristics suggest its osteoprogenitor nature [31].…”
Section: Discussionmentioning
confidence: 99%
“…Fresh samples of SC-EHAD tissue exhibited CD34− and CD45−phenotypes, while SC-EHAD cells at later passages exhibited, besides that, a CD105−, CD166−, and collagen type I+ phenotype. These findings suggest that SC-EHAD is a possible source of progenitor cells [31]. However, the properties of this human cell lineage when cultivated on different implant surfaces are yet unknown.…”
Section: Introductionmentioning
confidence: 98%
“…A 66.29% ± 25.04% mean root coverage was achieved by the NFBG technique compared to 73.50% ± 25.53% achieved by SCTG, with no statistical differences between groups. The mean percentage of root coverage attained with NFBG is comparable to GTR‐based root coverage (16.7%‐100%), but results in significantly greater clinical attachment level gain and reduction in PD, as shown before for GTR‐based root coverage, especially in areas showing ≥ 5 mm of recession . This is particularly important in the treatment of deep recession defects where greater buccal attachment loss is observed.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, our research group has isolated and characterized cells obtained from surgically created early healing alveolar defects (SC‐EHAD) in humans for the first time, based on the NFBG technique . Our findings suggested that SC‐EHAD is a possible source of progenitor cells, since cells obtained from healing bone granulation tissue were able to adhere to plastic, to express some markers of MSC, and to assume a spindle‐shaped morphology at earlier passages, showing alkaline phosphatase and mineralization activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation